2017
DOI: 10.1051/matecconf/201710104017
|View full text |Cite
|
Sign up to set email alerts
|

Iron ore deposits model using geoelectrical resistivity method with dipole-dipole array

Abstract: Abstract.Mining industry is an industry with very high risk (losses). In order that mining activities can be run well, then the potential of the Earth's resources must be known for sure. one of the Earth's resources of high economic value is the iron ore. Iron ore is rarely found in a free state in nature, it is usually associated with other minerals and exposed randomly. With these properties, iron ore needs to be modeled before doing mining activities in order to avoid large losses. Iron ore deposits can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The application of dielectric properties to predict other soil characteristics and deposits has been used by many researchers from various fields of interest. Octava and Yulhendra (2016), for example, have used geoelectric data to determine the deposits of iron ore in the soil (Octova and Yulhendra, 2016), while Paillet et al (2010) reported good relations were noted between the electrical resistivity with texture, wetness, and cation exchange capacity of the forest soils. Therefore, the application of the proposed dielectric measurement technique could be useful for the calculation of the soil wetness and the soil water loss at various fields of interest.…”
Section: Resultsmentioning
confidence: 99%
“…The application of dielectric properties to predict other soil characteristics and deposits has been used by many researchers from various fields of interest. Octava and Yulhendra (2016), for example, have used geoelectric data to determine the deposits of iron ore in the soil (Octova and Yulhendra, 2016), while Paillet et al (2010) reported good relations were noted between the electrical resistivity with texture, wetness, and cation exchange capacity of the forest soils. Therefore, the application of the proposed dielectric measurement technique could be useful for the calculation of the soil wetness and the soil water loss at various fields of interest.…”
Section: Resultsmentioning
confidence: 99%
“…The result of 2D ERI presented in profile 1 showed the presence of mineral ore in the form of hematite rock as shown in Figure 2. However, not all of hematite rocks containing iron mineral occupies the profile due to discontinuous nature of iron mineralization (Octova and Yulhendra, 2017). Based on the resistivity values in Table 1, the profile 1 is categorized into four layers.…”
Section: Resistivity Profilementioning
confidence: 99%
“…(5) where : ρ is the resistivity of the material (ohm-meter) L is the length (meters) R is the measured resistance (ohms) A is the cross-sectional area (meter2) because R = 𝑉 𝐼 , then the equation is obtained: (6) where :…”
Section: Basic Theorymentioning
confidence: 99%
“…The geoelectrical resistivity method has several measurement techniques related to the purpose of the measurement. These techniques include sounding, profiling, and offset sounding in previous research [4][5] [6]. The measurement using the sounding method aims to obtain information on the conductivity of the medium in the vertical direction (layered earth model).…”
Section: Data Acquisitionmentioning
confidence: 99%